2021
DOI: 10.1002/ijc.33680
|View full text |Cite
|
Sign up to set email alerts
|

Can breast cancer be stopped? Modifiable risk factors of breast cancer among women with a prior benign or premalignant lesion

Abstract: Physical inactivity, high postmenopausal body mass index, alcohol consumption and use of menopausal hormone therapy are established risk factors for breast cancer.Less is known about whether these factors influence the risk of progression of benign and premalignant breast lesions to invasive breast cancer. This registry-based cohort study was based on women with a precancerous lesion who were followed for breast cancer. The cohort consisted of 11 270 women with a benign lesion, 972 women with hyperplasia with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…Moreover, Li et al found that high body mass index, alcohol use, and high fasting plasma glucose were risk factors of breast cancer-caused mortality [ 15 ]. In parallel, a registry-based cohort study in Norway showed that alcohol use and tobacco smoking were associated with higher risk of breast cancer for women with benign breast diseases [ 23 ]. Up to now, it has been identified multiple modifiable risk factors of breast cancer including alcohol, obesity, younger age of menarche, older age of menopause, fewer childbearing, fewer breastfeeding, lower physical activity, and unhealthy lifestyles such as high fat consumption and low intakes of fruits, vegetables, and grains [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Li et al found that high body mass index, alcohol use, and high fasting plasma glucose were risk factors of breast cancer-caused mortality [ 15 ]. In parallel, a registry-based cohort study in Norway showed that alcohol use and tobacco smoking were associated with higher risk of breast cancer for women with benign breast diseases [ 23 ]. Up to now, it has been identified multiple modifiable risk factors of breast cancer including alcohol, obesity, younger age of menarche, older age of menopause, fewer childbearing, fewer breastfeeding, lower physical activity, and unhealthy lifestyles such as high fat consumption and low intakes of fruits, vegetables, and grains [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…GAPDH gene was used as housekeeping gene in this study, Table (1) refer to primers sequences TKTL1 (11). GAPDH( 12)…”
Section: Rna Extraction and Qpcrmentioning
confidence: 99%
“…Breast cancer is the most common type of cancer diagnosed among women worldwide, it is a heterogeneous disease at the molecular level (1). and is the second leading cause of cancer death among women around the world and in the United States, according to the American Cancer Society, 268,600 women have been diagnosed with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have depicted the association between daily physical activity and better health outcomes which further reduce the risk of lifestyle-based risk factors for cancer ( 75 , 78 81 ). The findings have revealed that physical exercise also lowers the chances of recurrence and is associated with a longer life expectancy in survivors ( 75 , 82 , 83 ). Although there is no direct link between physical activity and cancer risk reduction, however, the multiple interconnected physiological processes, which include sex hormones, insulin resistance and insulin levels, inflammation, oxidative stress, and adipokines, are believed to be involved in lowering the risk of tumorigenesis ( 84 86 ).…”
Section: Dietary Factors In Bc Incidence and Recurrencementioning
confidence: 99%